Enhancement of Liberica Coffee Quality by Wet Fermentation using Bacillus subtilis - Indra Lasmana Tarigan; Ericha Aulia; Heriyanti Heriyanti; Madyawati Latief; Sutrisno Sutrisno (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Coffee is a tree species in the Rubiaceae family and Coffea genus. One way to enhance the value of coffee commodities is by using fermentation technology. Fermentation can use probiotic bacteria found in mongoose digestive tracts, creating coffee with a unique taste and aroma. Bacillus subtilis is one of these bacteria, offering an alternative to those from mongoose. This study aimed to analyze the effects of fermentation using B. subtilis bacteria on the physicochemical and sensory properties of Liberica coffee. The study method included bacteria preparation, coffee fermentation, and testing. The samples' total phenolics, flavonoids, caffeine, and chlorogenic acid contents were estimated. The analysis was performed using UV-Vis and GC-MS spectrophotometers. The results revealed that the fermentation process using B. subtilis improved the sensory and physical qualities of the fermented Liberica coffee. The total values of phenolic and flavonoid contents and antioxidants of the fermented Liberica coffee were higher than that of the original coffee. GC-MS analysis exhibited compounds in the fermented coffee in which the highest was N-Dodecyl-N-(trifluoroacetyl)dodecanamide (C26H48F3NO2), with a retention time of 23.73 minutes and an area percentage of 18.96%. Moreover, the caffeine and chlorogenic acid of the fermented Liberica coffee was lower than that of the original coffee.